Phytochemical screening, membrane stabilizing activity and cytotoxicity of ethanol extract of swietenia mahagony leaf - Nadi, Fatem-Tuz-Zohora (BRAC University, 2015)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2015